Kulturpolitik in Thüringen Praktiken - Governance - Netzwerke - Flohr, Michael (Edition Politik, 2019)
A comprehensive analysis of the ways, networks and structures of cultural politics on state level which shows that cultural politics currently experience a crisis concerning their purpose and structure that is inherent in the system.